The spirit-paraclete in the Gospel of John - Johnston, George 1913-1997 (Society for New Testament Studies monograph series, 1970)
This book attempts to make a contribution to the New Testament doctrine of the Spirit, with special reference to the paraclete problem. Dr Johnston begins with the use of the word 'spirit' in the Gospel of John and treats it as primarily 'impersonal'. It denotes divine power or energy. God acts by his spirit, both to create and to redeem. The Fourth Evangelist shows Jesus as the incarnate Word, a man uniquely inspired, whose absence after death is compensated for by an outburst of spiritual powers in his Church. The paraclete is representative of God or of Christ, and the Johannine teaching is that no angelmediator, no holy 'spirit' like the Archangel Michael, can take Christ's place. But truly inspired leaders - acting as teachers, exegetes, martyrs - and the inspired Church itself as a communion of love do embody the spirit-paraclete and do continue to represent Jesus. Special attention is paid to recent research on this subject, mainly in the area of the Dead Sea Scrolls. Dr Johnston argues that in insisting that the true spirit-paraclete must always exalt and interpret Jesus of Nazareth as the final revelation of God in man, John was in fact combating heretical views